Problems of Access to Information in Archives: An Evaluation on Folder Summaries in the Directorate of State Archives - Sümbül, Sinan (Information World, 2025)
Archives, as institutions where important records of evidential value are collected, organized, and made accessible, are significant for scientific research. One of the processes performed to facilitate access to information in archives is the summarization of records. This article aims to contribute to addressing deficiencies in the record summaries within the State Archives and to resolving related issues concerning access to information. The scope of the study is limited to Arabic-script records related to libraries found in the Ministry of National Education collection within the Republican Archive of the Presidency of the State Archives. The research employed a qualitative methodology, utilizing a case study design. Document analysis, a qualitative research method, was applied, and the documentary scanning technique was used to obtain the relevant documents. The article investigates whether the record summaries comply with the classification guidelines set forth by the Prime Ministry Ottoman Archive Classification Instructions prepared by the General Directorate of State Archives. It also examines whether these summaries align with the descriptive standards established by international organizations such as the Society of American Archivists (SAA) and the International Council on Archives (ICA). As a result of the findings obtained from the study, it was revealed that there are problems of access to information due to the lack of information about the people and institutions in the summaries created for archival records. The unique aspect of this study lies in its focus on record summaries within the Directorate of State Archives from the perspective of information accessibility, providing insights into potential summary formats.